Pharmacotherapy and group cognitive behavioral therapy enhance follow-up treatment duration in gambling disorder patients. Issue 1 (December 2016) - Choi, Sam-Wook; Shin, Young-Chul; Youn, HyunChul; Lim, Se-Won; Ha, Juwon
Abstract Background Longer treatment duration is important for the successful treatment of gambling disorder (GD). This retrospective study investigated the factors and interventions that might enhance treatment duration in GD patients in South Korea. Methods A total of 758 outpatients with a primary diagnosis of GD, who were treated in a clinical practice from 2002 to 2011, were assessed by retrospective chart review. We compared the treatment duration according to pharmacotherapy and group cognitive behavioral therapy (CBT). Results Pharmacotherapy contributed to a longer duration of treatment maintenance, despite the patients' gambling severity (p < 0.001). Participation in group CBT (p < 0.001) and antidepressants (p = 0.009) were associated with a longer treatment duration after adjusting for age, depression, and gambling severity. The treatment maintenance duration was the longest in those receiving combined antidepressant pharmacotherapy and group CBT (F = 35.79, p < 0.001). Conclusions Group CBT and antidepressants seem to enhance treatment follow-up duration in GD patients. Additional studies are needed to advance GD prevention and treatment strategies.